Comparison of vaginal mesh repair with sacrospinous vaginal colpopexy in the management of vaginal vault prolapse after hysterectomy in patients with levator ani avulsion: a randomized controlled trial - Švabík, Kamil; Martan, Alois; Mašata, Jaromír; El-Haddad, Rachid; Hubka, Petr (Ultrasound in obstetrics & gynecology, 2014)
OBJECTIVE: To compare the efficacy of two standard surgical procedures for post-hysterectomy vaginal vault prolapse in patients with levator ani avulsion. METHODS: This was a single-center, randomized interventional trial, of two standard surgical procedures for post-hysterectomy vaginal vault prolapse: Prolift Total vs unilateral vaginal sacrospinous colpopexy with native tissue vaginal repair (sacrospinous fixation, SSF), during the period from 2008 to 2011. Entry criteria included at least two-compartment prolapse, as well as complete unilateral or bilateral levator ani avulsion injury. The primary outcome was anatomical failure based on clinical and ultrasound assessment. Failure was defined clinically, according to the Pelvic Organ Prolapse Quantification system, as Ba, C or Bp at the hymen or below, and on translabial ultrasound as bladder descent to 10 mm or more below the lower margin of the symphysis pubis on maximum Valsalva maneuver. Secondary outcomes were evaluation of continence, sexual function and prolapse symptoms based on validated questionnaires. RESULTS: During the study period, 142 patients who were post-hysterectomy underwent surgery for prolapse in our unit; 72 of these were diagnosed with an avulsion injury and were offered participation in the study. Seventy patients were randomized into two groups: 36 in the Prolift group and 34 in the SSF group. On clinical examination at 1-year follow-up, we observed one (3%) case of anatomical failure in the Prolift group and 22 (65%) in the SSF group (P < 0.001). Using ultrasound criteria, there was one (2.8%) failure in the Prolift group compared with 21 (61.8%) in the SSF group (P < 0.001). The postoperative POPDI (Pelvic Organ Prolapse Distress Inventory) score for subjective outcome was 15.3 in the Prolift group vs 21.7 in the SSF group (P = 0.16). CONCLUSION: In patients with prolapse after hysterectomy and levator ani avulsion injury, SSF has a higher anatomical failure rate than does the Prolift Total procedure at 1-year follow-up.
Keywords: Aged; Surgical Mesh; Treatment Outcome; Coitus; koitus; lidé středního věku; Vagina; senioři; stresová inkontinence moči; hysterektomie vaginální; prolaps pánevních orgánů; Postoperative Complications; nemoci anu; lidé; Middle Aged; průzkumy a dotazníky; Hysterectomy, Vaginal; Pelvic Floor; Female; chirurgické síťky; vagina; výsledek terapie; Surveys and Questionnaires; ženské pohlaví; Urinary Incontinence, Stress; Pain; Humans; pánevní dno; Valsalvův manévr; Anus Diseases; bolest; gynekologické chirurgické výkony; Pelvic Organ Prolapse; Valsalva Maneuver; pooperační komplikace; Gynecologic Surgical Procedures